Dual-role of PtCl2 catalysis in the intramolecular cyclization of (hetero)aryl-allenes for the facile construction of substituted 2, 3-dihydropyrroles and polyheterocyclic skeletons. Issue 44 (4th May 2017) - Zhang, Yan-Yan; Wei, Yin; Tang, Xiang-Ying; Shi, Min
Abstract : A novel PtCl2 -catalyzed cyclization of (hetero)aryl-allenes has been developed, providing controllable and facile synthesis of substituted 2, 3-dihydropyrroles and polyheterocyclic skeletons in moderate to good yields. Abstract : A Pt(ii )-catalyzed cyclization of (hetero)aryl-allenes has been developed, providing controllable synthesis of substituted 2, 3-dihydropyrroles and polyheterocyclic skeletons. Another notable feature of this method is the dual-role of the Pt(ii ) catalyst: initiation of the migration of the (hetero)arylmethylene group and the subsequent Friedel–Crafts type annulation.